The Socio–Juridical Dimensions of Passing Off in Indonesia - Baso, Fatihani; Djaoe, Andi Novita Mudriani; H, Redita Septia Sari (Dialogia Iuridica, 2023)
There are many business actors marketing products that resemble well-known brands in Indonesia. To prove whether the Passing Off phenomenon occurs or not in Indonesia, the authors use The Classical Trinity Theory. The article’s aim is to explain the socio–juridical dimensions of passing off in Indonesia. Seeing that in Indonesia there are many business actors marketing products that resemble well-known brands. To prove whether the Passing Off phenomenon occurs or not in Indonesia, the author uses The Classical Trinity Theory. The research uses a juridical-normative method, with statute and conceptual approach based on literature study, analyzed qualitatively. The Classical Trinity Theory is a theory used as a basis for assessment which states whether a passing-off action occurred or not. First, Goodwill, is whether business actors use the reputation of well-known brand owners to support their business. Second, misrepresentation, there is confusion by consumers regarding genuine products and fake products. Third, damage, there is an element of deceptive branding and goods or services which could very well result in losses experienced by the owner of the well-known brand as a result of copying the company’s identity.